The correlation between sleep bruxism, salivary cortisol, and psychological status in young, Caucasian healthy adults - Fluerașu, Mirela Ioana; Bocsan, Ioana Corina; Buduru, Smaranda; Pop, Raluca Maria; Vesa, Stefan Cristian; Zaharia, Alina; Negucioiu, Marius; Iacob, Simona Maria (Cranio, 2021)
: To analyze the association between sleep bruxism (SB), salivary cortisol, and psychological state in healthy adults. : Sixty healthy students (with or without SB) were included in the study. The subjects completed a questionnaire that evaluated the presence of SB and analyzed the general and work-related psychological states and job-related frustration. Clinical examinations of TMJs and dental wear were performed. The salivary cortisol was determined using ELISA technique. : Subjects with SB had a general status characterized by anxiety or stress compared to subjects without SB. They also presented a work-induced depressive or anxious attitude compared to healthy individuals. The salivary cortisol levels were higher in subjects with SB and in females and were correlated with subjects' general anxiety, but not with a job-induced psychological state. : SB is correlated with general and job-induced psychological changes. Salivary cortisol could be a non-invasive marker for the evaluation of SB severity.